Preservation of Human Mesenchymal Stromal Cells in Protein-Supplemented Alginate Capsules - Hubenia, Oleksandra; Leal Marin, Sara; Trufanova, Natalia (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):285